Agreement in Measures of Macular Perfusion between Optical Coherence Tomography Angiography Machines - Dai, Wei; Chee, Miao-Li; Majithia, Shivani; Teo, Cong Ling; Thakur, Sahil; Cheung, Ning; Rim, Tyler Hyungtaek; Tan, Gavin S.; Sabanayagam, Charumathi; Cheng, Ching-Yu; Tham, Yih-Chung (Scientific reports, 2020)
We evaluated the agreements in foveal avascular zone (FAZ) area and vessel density (VD) parameters (within the superficial capillary plexus region), between two widely used optical coherence tomography angiography machines. Participants who attended the Singapore Malay Eye Study III between 29th March and 6th August 2018, were enrolled in this study. Participants underwent fovea-centered 6×6-mm macular cube scan, using both AngioVue and Cirrus HDOCT machines. Scans were analyzed automatically using built-in review software of each machine. 177 eyes (95 participants) without retinal diseases were included for final analysis. Mean FAZ area was 0.38 ± 0.11 mm 2 and 0.30 ± 0.10 mm 2 , based on AngioVue and Cirrus HDOCT, respectively. Mean parafoveal VD was 0.50 ± 0.04 in Angiovue, and 0.43 ± 0.04 in Cirrus HDOCT. Cirrus HDOCT measurements were consistently lower than those by AngioVue, with a mean difference of −0.08 (95% limits of agreement [LOA], −0.30–0.13) mm 2 for FAZ area, and −0.07 (95% LOA, −0.17–0.03) for parafoveal VD. Intraclass correlation coefficients for FAZ area and parafoveal VD were 0.33 and 0.07, respectively. Our data suggest that agreements between AngioVue and Cirrus HDOCT machines were poor to fair, thus alternating use between these two machines may not be recommended especially for follow up evaluations.